ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PEMILIHAN KARIR SEBAGAI DOSEN BAGI MAHASISWA AKUNTANSI (STUDI KASUS PADA FAKULTAS EKONOMI JURUSAN AKUNTANSI DI UNIVERSITAS BANGKA BELITUNG) - Rulyanti Susi Wardhani; Ivan Lesmana (Jurnal Akuntansi Bisnis, 2017)
An Analysis of Faktor that Influence the Accounting Students to Select Their Career as a Lecturer (A Case study at Economic Faculty of  Bangka Belitung University).This study aims to determine the effect of intrinsic value of work, income, availability of work opportunities, work environment, sacrifice of profession, skills, and work understanding to career selection of accounting students being a lecturer. Primary data is collected from the field. Samples are 119 students using Slovin formula and analyzed by factor analysis.The analysis yields there are two factors affecting the career selection of accounting students being a lecturer. First, job information consisted of some variables such as income, availability of work opportunities, and work understanding. Second, personality consisted of work intrinsic value and work environment. There is relation between those factors showed by the result of analisis factor in which the magnitude of both is high enough over 0.5 (50%). The amount of the first factor is 65% and the second one is 57.9%. So, it can be concluded that the most dominant factor is the first factor (job information).Keyword : intrinsic value of work, income, availability of work opportunities, work environment, sacrifice of profession. Skills, work understanding, personality.